The assessment of mental health literacy and mental health factors among college students - Asidik, Azip Hasbi; Prabandari, Yayi Suryo; Setiyawati, Diana (BKM Public Health and Community Medicine, 2022)
Purpose: To assess mental health literacy, mental health conditions, and mental health factors among college students to support the implementation of Health Promoting University. Methods: This research utilized Explanatory Sequential Mixed Methods using data collected from 431 college students and interviewed eight college students. The instrument used a self-report online questionnaire and a semi-structured interview guide. Data analysis used logistic regression and thematic analysis. Results: Almost half of the college students (48.96%) had low mental health literacy. In the amount of 61.95% of students had mental health problems. Factors that significantly had relationships with mental health were a child maltreatment history (AOR:2.46; 95%CI:1.62-3.73; p-value<0.001) and poor friends interaction (AOR:1.64; 95%CI:1.02-2.63; p-value=0.039) after adjusting for sex, mental health literacy, physical activity, allowance, habitation, and academic interaction. Mental health literacy in college students qualitatively does not recognize the specific types of mental health problems and mental health services. Qualitatively, mental health factors that were most mentioned were child maltreatment history, poor friend interaction, and environment. Conclusion: Almost half of the college students have low mental health literacy and do not recognize the types of mental health problems and mental health services. Mental health problems were common among college students. Campuses need to improve mental health literacy and an environment that supports mental health.